ORIGINAL ARTICLE DILEMMAS, RISKS AND FAMILIAL IMPLICATIONS OF LIVING IN HIV SERODISCORDANT RELATIONSHIPS, JIMMA TOWN/OROMIA - Jibat, Nega; Nigussie, Berihanu; Tesfaye, Selamawit (European Scientific Journal, ESJ, 2014)
Till recently, serodiscordant couples were ignored though HIV negative sexual partners and children born in the relationship are at high risk of infection. Difficulty of making decision with respect to divorce, child bearing, and managing sexual patterns characterize serodiscordants. In Ethiopia, most infected married people are serodiscordant and do not mutually know their HIV status. Lack of adequate studies on serodiscordance necessitates this study to identify people’s perceptions and practices concerning serodiscordance. In-depth interview with serodiscordant couples and key-informant interviews with health care providers, and thematic analysis were employed to gather and analyze the information respectively. Serodiscordant couples know their HIV status lately after they have developed health complications; practice unsafe sex and give birth to infected child. Confusions are observed among discordant couples and health care providers on the possibility of future infection of the negative partner and the etiology of serodiscordance in general. The explanations are inconsistent and some are erroneous. Difficulty of managing familial relationships, the dilemma of child bearing, risk of child infection, forced changes in patterns of sexuality, lack of social support, and unreliable livelihood are among the challenges they face. Negative HIV partners and children born to serodiscordant couples are at risk of infection. Yet serodiscordance is not given adequate attention in HIV/AIDS care and prevention public programs. Programs targeting married people and serodiscordant couples are necessary to curb Mother to Child Transmission.